Assessment of public participation process in the comprehensive integrated transport planning process of the City of Johannesburg : 2003-2013 - Phala, Seraki Victor (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPA)--Stellenbosch University, 2019.